Life lines : (Oxford University Press, 1997)
The book features a clear, comprehensive, yet manageable language syllabus, a discovery approach to the presentation of language, motivating texts from a variety of authentic sources, strong skills development with an emphasis on functional English, systematic vocabulary work recycled within the unit, a pronunciation syllabus introducing sounds, stress and intonation, optional Extension sections at the end of each unit. The Workbook has with key and without key versions. It contains further practice of the language and vocabulary presented in the Student's Book, an independent writing syllabus and Grammar Check sections